The Importance of Local Communities in Environmental Conservation and Natural Resource Management for Ecosystem and Economic Sustainability - Ramle, Nur Laila Binti; Mardikaningsih, Rahayu; Halizah, Siti Nur (Bulletin of Science, Technology and Society, 2022)
Community-based conservation has become an important strategy to preserve the environment and improve the socio-economic welfare of local communities. This research aims to analyze the role of local communities in natural resource management as well as the factors that influence the effectiveness of community-led conservation initiatives. Using a literature review approach, this research evaluates how active community involvement in conservation can improve ecological and economic resilience. The results show that community-based conservation practices, such as forest management and sustainable ecotourism, are able to maintain biodiversity and provide economic benefits to local communities. The integration of traditional knowledge and scientific approaches has been shown to improve the effectiveness of natural resource management. Many challenges remain, including limited resources, lack of legal recognition, and economic pressures that can hinder the sustainability of conservation programs. More supportive policies, such as recognizing community ownership rights to conservation areas and providing economic incentives, are needed to ensure the sustainability of these initiatives. Partnerships between communities, government, non-governmental organizations and the private sector can strengthen communities' capacity to manage natural resources sustainably. With the right support, community-based conservation can be an effective solution to achieve a balance between environmental protection and improved community welfare.